Comparative Genomics of a Bovine Mycobacterium tuberculosis Isolate and Other Strains Reveals Its Potential Mechanism of Bovine Adaptation - Xuekai Xiong; Xuekai Xiong; Rui Wang; Dachuan Deng; Dachuan Deng; Yingyu Chen; Yingyu Chen; Han Liu; Han Liu; Tianqi Wang; Tianqi Wang; Jieru Wang; et al. (Frontiers in Microbiology, 2017)
The Mycobacterium tuberculosis complex causes tuberculosis (TB) in humans and other animal species, but Mycobacterium tuberculosis has a distinct host preference to humans. The present study aimed to determine whether a bovine M. tb strain 1458 has evolved some genetic properties in their genome that might be associated with their bovine adaptation. The genome of the M. tb strain 1458 was sequenced and subjected to an extensive comparative genomic analysis. A phylogenetic analysis showed that strain 1458 is most closely related to a Chinese M. tb strain, CCDC5079, of the same Beijing family. Compared with three human M. tb Beijing family strains, the strain 1458 has the fewest unique genes. However, there are most (21) IS6110 insertion sequences in the strain 1458 genome at either intragenic or intergenic sites, resulting in the interruption of 11 genes including three PPE family-encoding genes (PPE16, PPE38, and PPE59). Only the strain 1458 genome has the upstream insertion in esxS and phoP genes. PCR confirmed four upstream insertions and qPCR determined that transcription of esxS, phoP, dnaN, and ctpD genes differed significantly between M. tb strain 1458 and H37Rv or M. bovis. A Kyoto Encyclopedia of Genes and Genomes pathway enrichment analysis revealed that the genes affected by non-synonymous SNPs are enriched in RNA polymerase. Moreover, 127 of the 133 unique SNPs in strain 1458 are either different to those in the M. bovis genome. In conclusion, some critical genes responsible for bacterial virulence and immunogenicity were interrupted in the genome of bovine M. tb strain 1458 by IS insertions and non-synonymous SNPs, which might contribute to its bovine adaptation, and the modification of its virulence and immunogenicity in cattle.